Party system transformation from below: protests by Jobbik and LMP - Endre Borbáth; Pál Susánszky (Acta Politica, 2025)
Recent changes in European politics—such as the rise of so-called movement parties on both the left and the right—call for a rethinking of the links between protest dynamics and party system transformation. In this paper, we contribute to the theoretical and empirical understanding of the mechanisms that unfold in periods of intensified interactions between protest and electoral politics through a case study of the transformation of the Hungarian party system. We ask what mechanisms drive parties' involvement in protests before and after entering parliament. We focus on two competitors: the radical right Movement for a Better Hungary (Jobbik) and the green party Politics Can Be Different (LMP). Using a dataset of protest events compiled from Hungarian news agency reports and official police records, we map the protest network mobilized by the two parties between 2002 and 2022. We analytically distinguish and empirically identify three different mobilization mechanisms: strengthening the party's profile by protesting its own issue, using protest mobilization to build alliances with other parties and actors, or relying on protest to establish a presence at the local level. The empirical results show that Jobbik relies on protest through a combination of different mechanisms, while LMP uses protest to broaden its issue profile and build alliances with other political parties. Over time, both parties increasingly rely on protest to establish a local presence outside of Budapest.
Keywords: 320; Movement parties; Protest; Jobbik; LMP; Network analysis; Protest event analysis